2011
DOI: 10.1128/aem.06438-11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glucose on the Fatty Acid Composition of Cupriavidus necator JMP134 during 2,4-Dichlorophenoxyacetic Acid Degradation: Implications for Lipid-Based Stable Isotope Probing Methods

Abstract: Combining lipid biomarker profiling with stable isotope probing (SIP) is a powerful technique for studying specific microbial populations responsible for the degradation of organic pollutants in various natural environments. However, the presence of other easily degradable substrates may induce significant physiological changes by altering both the rate of incorporation of the target compound into the biomass and the microbial lipid profiles. In order to test this hypothesis, Cupriavidus necator JMP134, a 2,4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…The similarity of the total FAME amounts in both treatments (with or without sand) suggested that there was no difference in the total microbial biomass. Spectrophotometric measurements of the bacterial density in the liquid phase showed that C. necator JMP134 cultures in the presence of 2,4-D presented similar growth as reported previously (Lerch et al, 2007 , 2011 ). For both treatments, the exponential phase reached its maximum after 3 days followed by a stationary phase that lasted for the next 2 days.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The similarity of the total FAME amounts in both treatments (with or without sand) suggested that there was no difference in the total microbial biomass. Spectrophotometric measurements of the bacterial density in the liquid phase showed that C. necator JMP134 cultures in the presence of 2,4-D presented similar growth as reported previously (Lerch et al, 2007 , 2011 ). For both treatments, the exponential phase reached its maximum after 3 days followed by a stationary phase that lasted for the next 2 days.…”
Section: Discussionsupporting
confidence: 85%
“…Variations in the lipid biomarker composition are not only due to the modification of the microbial composition but also to physiological changes. For example, the sensitivity of FAME profiles to change in growth substrate has been reported (Lerch et al, 2011 ). According to the present study, the bacterial sessile mode of life also alters the signature of lipid biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, a number of bacterial strains utilizing 2,4-D have been reported, such as A. xylosoxidans EST4002, 23 Arthrobacter sp., 35 Bradyrhizobium sp. HW13, 36 B. elkanii USDA94, 37 Burkholderia cepacia DS-1, 17 C. necator JMP134, 28 C. campinensis BJ71, 38 Cupriavidus sp. TFD33, 39 Novosphingobium DY4, 40 Pseudomonas sp.…”
Section: ■ Discussionmentioning
confidence: 99%
“…3,26 C. necator JMP134 could degrade 70% of 2,4-D at 250 mg L −1 in 10 days, and its degradation rate was 17.5 mg L −1 day −1 . 28 Although numerous strains have been reported to degrade 2,4-D, it would be still valuable for acquiring novel and fast…”
Section: ■ Introductionmentioning
confidence: 99%